Effect of watering frequencies on physio-chemical of Hevea Brasiliensis seedling under glass house condition - Abd Halim, Mohd Khairil Hilmi (2013)
Currently, about 1.25 million hectare of area in Malaysia is planted with rubber tree with output 1.2 million ton of natural rubber per year. The government aims to increase the production of rubber to 1.8 ton per hectare for the coming year 2012 (Malaysia Rubber Board, 2010).Development sector is now closing in many potential lands for rubber planting. Realizing the fact that limited land is available for planting in Malaysia, the best way to increase the production and among the farmers is by increasing the productivity of rubber. Thus, this study was carried out to analyse the ability of RRIM 3001 clones to survive in water stress based on water frequency and towards difference soil series, which is Munchong series, Serdang series and Sg Buloh. The other objective is to determine the effect of physiological changes of plant under different soil and to investigate the effect of different growth of rubber plant under different water stress. The seedling used in this study were RRIM 3001. The study started in January 2013 and ended in Jun 2013. Five treatment were used in this study to investigate watering frequency, i.e. every day, two days and four days, sixth days and eight days. The experimental design was a Randomized Complete Block Design (RCBD) with tree replications and fifteen treatments. The data were recorded and analyzed with Analysis of Variance (ANOVA) and Least Significant Different (LSD) for mean comparison using Statistical Analysis System (SAS) statistical package for determining the effect of clones and watering frequency on the plants growth. The result from this study showed the characteristics used to determined water stress in RRIM 3001 and towards difference soil such as girth circumference, leaf area, height, stomata conductance and chlorophyll content, showed T1, well-water has highest and T15, least watered has lowest value at every treatment. Based on this experiment, Munchong Series is the best soil while Sg Buloh series is the least suitable soil for rubber seedlings.